Integrating Sustainability Science in Maritime Vocational Education: Professional and Graduate Perspectives - Pongoh, Frisca Mareyta; Saifudin, Iksan; Silalahi, Aliong; Alamsyah, Jaya (Meteor STIP Marunda, 2025)
This research explores the integration of transdisciplinary and sustainability science into maritime vocational education to enhance ecosystem resilience. Drawing on qualitative data from five maritime professionals, five lecturers, and fifteen senior cadets from the Maritime Polytechnic of North Sulawesi, this study captures the depth of experience and expertise across industry, academia, and student perspectives. The findings reveal that ecosystem resilience education—when supported by industry-based learning, environmental case studies, and interdisciplinary methods—equips maritime cadets with holistic skills necessary for addressing real-world challenges. By understanding the connections between marine ecosystem health, shipping logistics, and sustainable economic practices, the study underscores the need for curriculum reform that promotes systemic thinking. The research emphasizes how knowledge co-production between practitioners and educators can lead to more inclusive, socially just, and sustainable maritime education. These insights are especially critical for maritime institutes preparing graduates to operate within global sustainability frameworks and green economy initiatives.